A hybrid controller for multi-agent collision avoidance via a differential game formulation - Cappello,D; Garcin,S; Mao,Z; Sassano,M; Paranjape,A; Mylvaganam,T (IEEE Transactions on Control Systems Technology, 2021)
We consider the multi-agent collision avoidance problemfor a team of wheeled mobile robots. Recently, a local solutionto this problem, based on a game theoretic formulation, has beenprovided and validated via numerical simulations. Due to itslocal nature the result is not well-suited for online application.In this paper we propose a novel hybrid implementation of thecontrol inputs that yields a control strategy suited for the onlinenavigation of mobile robots. Moreover, subject to a certain dwelltime condition, the resulting trajectories are globally convergent.The control design is demonstrated both via simulations andexperiments.